Patient and Health worker experiences on Utilization of Community Client Led ART Delivery Model in South-Western Uganda: A Qualitative Study - Kintu, Timothy Mwanje; Ssewanyana, Anna Maria; Kyagambiddwa, Tonny; Nampijja, Pretty Mariam; Apio, Patience Kevin; Kitaka, Jessica; Kabakyenga, Jerome Kahuma (Research square, 2021)
Background: In an effort to accommodate the growing number of stable HIV clients, improve retention in care and reduce health care burden the differentiated service delivery (DSD) models were introduced in 2014. One such model, Community Client Led ART Delivery (CCLAD) was rolled out in Uganda in 2017. The extent of utilization of this model has not been fully studied. The aim of the study was to explore the patient and health worker experiences on the utilization of CCLAD model at Bwizibwera Health Centre IV, south western Uganda. Methods: This was a descriptive study employing qualitative methods. The study had 68 purposively selected participants who participated in 10 Focus Group Discussions with HIV clients enrolled in CCLAD; 10 in-depth interviews with HIV clients not enrolled in CCLAD and 6 health workers. Key informant interviews were held with the 2 focal persons for DSD. The discussions and interviews were audio recorded, transcribed verbatim and then translated. Both deductive and inductive approaches were employed to analyse the data using in NVivo software. Results: Patient and health worker experiences in this study were categorized as drivers and barriers to the utilization of the CCLAD model. The main drivers for utilization of this model at different levels were: individual (reduced costs, living positively with HIV, improved patient self-management), community (peer support and contextual factors) and health system (reduced patient congestion at the health centre, caring health workers as well as CCLAD sensitization by health workers). However, significant barriers to the utilization of this community-based model were: individual (personal values and preferences, lack of commitment of CCLAD group members), community (stigma, gender bias) and health system (frequent drug stockouts, certain implementation challenges, fluctuating implementing partner priorities, shortage of trained health workers and insufficient health education by health workers). Conclusion: Based on our findings the CCLAD model is meeting the objectives set out by Differentiated Service Delivery for HIV care and treatment. Notwithstanding the benefits, challenges remain which call on the Ministry of Health and other implementing partners to address these hindrances to facilitate the scalability, sustainability and the realization of the full-range of benefits that the model presents.
Keywords: CCLAD; Utilization; HIV; Uganda; Differentiated service delivery; Client-led; ART delivery